S. García Dauder y E. Pérez Sedeño, Las “mentiras” científicas sobre las mujeres - José Antonio Díez Calzada; Núria Sara Miras Boronat (Crítica)
S. García Dauder y E. Pérez Sedeño, Las “mentiras” científicas sobre las mujeres, Los Libros de la Catarata, Madrid, 2017, 256 pp.